THEORETICAL ISSUES OF MONETARY POLICY INSTRUMENTS (Conferencea, 2024)
In developed countries such as the United States, Japan and Germany, the central banks have accumulated many years of theoretical, practical and methodological experience in ensuring and strengthening economic growth, macroeconomic and financial stability based on increasing economic and investment activity through the effective use of monetary policy various monetary models are effectively used in its activities.